Perguntas-respostas em textos escritos: uma análise no âmbito das relações discursivas - Mendes, Amália; Lejeune, Pierre; Nunes, Carolina (Revista da Associação Portuguesa de Linguística, 2020)
Question-answer pairs are typically associated to spoken discourse and to directive speech acts, although they are also found in written texts. We analyse contexts extracted from the CRPC-DB, a written subcorpus annotated with discourse relations in the PDTB-style. We focus on the nature of the question and of the answer in interactional contexts, but also in contexts where a single locutor poses the question and answers it. Contexts of question-answer pairs with a single locutor have a textual function related to the topic-comment structure of the text and involve a virtual locutor and a modalized assertion. We discuss the treatment of question-answer pairs in discourse banks following different theoretical frameworks and make a proposal that integrates these contexts in our annotation scheme. Our results contribute to theoretical proposals that focus on the pragmatic and textual functions of question-answer pairs, and their application to a new resource for the study of discourse in Portuguese.